2007
DOI: 10.3168/jds.s0022-0302(07)71585-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oils Rich in Linoleic and Linolenic Acids to Enhance Conjugated Linoleic Acid in Milk from Dairy Cows

Abstract: Forty Holstein dairy cows were used to determine the effectiveness of linoleic or linolenic-rich oils to enhance C18:2 cis-9, trans-11 conjugated linoleic acid (CLA) and C18:1 trans-11 (vaccenic acid; VA) in milk. The experimental design was a complete randomized design for 9 wk with measurements made during the last 6 wk. Cows were fed a basal diet containing 59% forage (control) or a basal diet supplemented with either 4% soybean oil (SO), 4% flaxseed oil (FO), or 2% soybean oil plus 2% flaxseed oil (SFO) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
155
3
23

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(228 citation statements)
references
References 37 publications
47
155
3
23
Order By: Relevance
“…Our results concur with those of Wu et al (1993) and Bu et al (2007) in cows. Other studies, using saturated or protected fats (Grummer, 1991;Palmquist and Beaulieu, 1993, in cows;Pérez Alba et al, 1997;Gargouri et al, 2006, in sheep), report an increase in the percentage of milk fat.…”
Section: Discussionsupporting
confidence: 83%
“…Our results concur with those of Wu et al (1993) and Bu et al (2007) in cows. Other studies, using saturated or protected fats (Grummer, 1991;Palmquist and Beaulieu, 1993, in cows;Pérez Alba et al, 1997;Gargouri et al, 2006, in sheep), report an increase in the percentage of milk fat.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, C18:1 trans-11 and C18:2 cis-9, trans-11 (biohydrogenation intermediate isomers) were increased in rumen contents with SO compared with control and HPO. This is important for milk production because those FA can escape from the rumen and be secreted in milk as shown by Bu et al (2007) who observed increases in the C18:1 trans-11 and C18:2 cis-9, trans-11 concentrations of milk fat when dairy cows were supplemented with vegetable oils and oilseeds rich in C18:2 cis n-6.…”
Section: Discussionmentioning
confidence: 99%
“…Because the lactation period is characterized by a demand for the nutrients required for milk production and is associated with a limited capacity for food intake, feeds with high nutrient content can often be used during early lactation to compensate for this lower intake and to ensure continued productivity (Bu et al 2007). …”
mentioning
confidence: 99%